2017
DOI: 10.2196/publichealth.7129
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trials of Technology-Based HIV/STI and Drug Abuse Preventive Interventions for African American and Hispanic Youth: Systematic Review

Abstract: BackgroundHIV/sexually transmitted infections (STIs) and drug abuse remain significant public health concerns in the United States, and African American and Hispanic youth are disproportionately affected. Although technology-based interventions are efficacious in preventing and reducing HIV/STI and licit/illicit drug use behaviors, relatively little is known regarding the state of the science of these interventions among African American and Hispanic youth.ObjectiveThe aim of this review is to identify and exa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…Finally, a review of rigorously tested (e.g. randomized controlled trial), technology-based, behavioral HIV prevention interventions for Black and Latino youth identified only 2 studies [54]. Thus, the quantity, and perhaps the quality, of HIV prevention interventions targeting adolescents in general are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a review of rigorously tested (e.g. randomized controlled trial), technology-based, behavioral HIV prevention interventions for Black and Latino youth identified only 2 studies [54]. Thus, the quantity, and perhaps the quality, of HIV prevention interventions targeting adolescents in general are limited.…”
Section: Introductionmentioning
confidence: 99%
“…STI/HIV testing, and the prevention and reduction of drug use and sexual risk behaviors remain important strategies to prevent HIV among youth in the United States [40]. However, the scientific knowledge remains limited with respect to scalable mHealth solutions to improve uptake of STI and HIV testing and the prevention and reduction of drug use and sexual risk behaviors among youth [16]. Compared to AIDS service organizations and adult-focused clinics, youth are more likely to seek drug abuse and STI/HIV prevention and risk reduction services from youth-centered community health clinics [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, our design in the present study does not allow us to formally test S4E’s potential mechanisms of change. Few researchers have determined the pathways through which youth behavior changes occur, especially regarding technology-based interventions [16]. Therefore, future research examining the utility of this framework in an experimental design to test the hypothesized mechanisms of change is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that mHealth-based intervention approaches may be particularly salient for technology savvy youth, but also a promising method to increase reach to key populations with educational information, digital media, and/or game-based learning, aimed at reducing HIV risk behaviors [5,6]. In a review of mHealth interventions for high risk MSM, Schnall and colleagues found that web-based videos and education modules reduced HIV risk behavior and promoted HIV testing [7].…”
Section: Introductionmentioning
confidence: 99%